2022
DOI: 10.1111/inm.13075
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to mental health effect among nursing students in Japan and the United States during the coronavirus pandemic: A cross‐sectional study

Abstract: In the context of mental health, university students have been considered a vulnerable population. However, limited studies have underscored the association between preventive health behaviour levels and mental health effects among nursing students. The current cross‐sectional study provides a comparative analysis of the impact of mental health factors on nursing students in Japan and the United States (US) in the context of the coronavirus disease 2019 (COVID‐19) pandemic. The study consisted of 878 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…It is suggested that educational managers should strengthen the self-esteem, and self-worth of professional degree graduate students, improve the acceptance of risk information to promote health behavior change, and pay close attention to their depression, anxiety, and other emotional changes. The outcomes of this study are similar to the results of Kondo’s study that Japanese students have a higher level of mental health compared with those in the United States [ 57 ]. Some studies have also found that graduate students have better mental health than undergraduates before and during the COVID-19 pandemic [ 58 ].…”
Section: Discussionsupporting
confidence: 88%
“…It is suggested that educational managers should strengthen the self-esteem, and self-worth of professional degree graduate students, improve the acceptance of risk information to promote health behavior change, and pay close attention to their depression, anxiety, and other emotional changes. The outcomes of this study are similar to the results of Kondo’s study that Japanese students have a higher level of mental health compared with those in the United States [ 57 ]. Some studies have also found that graduate students have better mental health than undergraduates before and during the COVID-19 pandemic [ 58 ].…”
Section: Discussionsupporting
confidence: 88%
“…In another study, we reported the factors related to mental health among both undergraduate and graduate nursing students in Japan and the United States; the results indicated that perceived control, not only at the individual level but also at the policy level, can buffer the mental health effects caused by preventive behavior during the COVID-19 pandemic. However, this study excluded international students due to the small number of international students in the nursing department ( 35 ). Therefore, we further collected data from medical and dental graduate students.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they were more stressed/depressed because of social distancing and stay‐at‐home measures compared with their American counterparts. Lower levels of perceived control may be related to Japan's culture that is collectivistic and values networks, such as respecting others' wishes and feelings and conforming rather than individualism (Hornsey et al, 2019); therefore, it was considered that these Japanese cultural features could be related to the nursing students' more preventive behaviors and worsening mental health (Kondo et al, 2023). It is unknown, however, whether various levels of sociodemographic factors related to perceived control and preventive behaviors are different between Japanese and American nursing students.…”
Section: Introductionmentioning
confidence: 99%